Analisis Pengendalian Internal atas Persediaan Sparepart pada PT Bina Pertiwi Cabang Makassar - Rangga, Agustina; Kacing, Carolina Olivia (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
The purpose of this study is to evaluate how effectively the internal control system manages the spare parts inventory at the Makassar branch of PT Bina Pertiwi system used by the companyincludes the FIFO (First In First Out) method to maintain the quality of spare parts and SAP(System Application and Product) that manages stock in real-time and supports automatic order through the SO system. (Stock Order). This study adopts a qualitative methodology that involves direct observation and interviews with warehouse and logistics staff at PT Bina Pertiwi. The findings of this study suggest that the internal control system in place is operating effectively, reducing the risk of damage to spare parts due to prolonged storage, and enhancing efficiency in inventory management.